Productive behavior and nutritional value of 22 genotypes of ryegrass (Lolium spp.) on three high Andean floors of northern Peru - Vallejos-Fernández, Luis A. (2020)
The dairy activity, based on pastures, represents the main source of income for the rural population of the Andes of northern Peru. The objective was to evaluate biomass yield, growth rate, plant height, Crude Protein (CP), Neutral Detergent Fiber (NDF), in vitro digestibility of dry matter (IVDDM) and metabolizable energy (ME) of 22 genotypes of Lolium spp. in three Andean floors (AF) (AF I: 2300 - 2800, AF II: 2801 - 3300 and AF III: 3301 - 3800 masl) in northern Peru. Better biomass (7662 kg dry material (DM) ha-1 year-1) and growth rate (21.0 kg DM ha-1 day-1) showed AF I for Lolium perenne L., however AF III stood out in yield (9,041 kg MS ha-1 year-1) and growth rate (24.8 kg DM ha-1 day-1) for Lolium multiflorum L. The mean ME was 2.61 Mcal kg-1 MS and 2.43 Mcal kg-1 MS for L. perenne and L. multiflorum, respectively. The nutritional values of both varieties are adequate for feeding cattle to grazing in the mountains. Likewise, the genotypes that showed better performance should be used in a pasture improvement plan.